The Diversity and Conservation of Piper (Piperaceae) in Bukit Barisan Selatan National Park, Lampung Province - Munawaroh, Esti; ., Yuzammi (Media Konservasi, 2018)
Piper (Piperaceae) is an aromatic plant genus, some species of which can also be used as ornamental plants. We have carried out plant exploration in Bukit Barisan Selatan National Park (TNBBS) of Lampung Province, which is known as one of the centres of diversity for Piper species. This field exploration aimed to contribute to the inventory of Piper species in Sumatera. A purposive sampling method was employed. The work was carried out from 2011 to 2014 in four resorts of TNBBS, viz. Kubu Perahu Resort, Sukaraja Atas Resort, Pugung Tampak Resort and Sekincau Resort. The results revealed that there are 21 Piper species present in TNBBS; of which one species is a tree, six species are shrubs, and the other 14 species are climbers. All these species have been cultivated as collections in Bogor Botanic Gardens (West Jawa Province) and also in Liwa Botanic Garden (West Lampung Province), for ex-situ conservation purposes. Results of analysis of morphological characters are discussed along with information about the usage of the species. A key to the species and maps showing their distribution are presented in the paper.Keywords: Bukit Barisan Selatan National Park, exploration, Piper spp.